Social Pathology of Trust in Car Written Manuscripts - Divsalar, Farhad; Nemati, Azadeh (Richtmann Publishing, 2012)
Poetry can be considered as a means of expressing emotions and also represents the personality, beliefs, and even socialclass. From poems proposed one can get others emotional status at the moment. Normally we recite happy songs when we are in agood mood and definitely by expressing sad verses we convey our unhappiness. This is actually a kind of emptying positive or negativeenergy and is seen in all members of society. Among these members of society are the car owners, from whose written on car manyideas can be revealed. Car written manuscripts are part of culture and folklore of people so, by studying them, culture of ordinary peoplecan be detected. To express the feelings and ideas car owners use these verses, also they can communicate in this way with ordinarypeople without considering the style of poems. Sometimes, these verses teach a lesson and to tell the truth its effect is more, as there isno bitterness of advice and as a result it is a kind of moral literature. Present article indicates a new research in the field of pathologyanalysis of social trust which present in car written manuscripts. It seems that the lack of attention to the important factors of humanpersonality cause mistrust in the community. Some of these factors such as, hopelessness, ignorance, greediness, jealousy and … willbe tackled in this article.